Teachers’ Acceptance towards the Inclusive Education Program for Students with Hearing Impairment - Rohaizat Ibrahim; Liyana Abd Talib (Department of Special Education, 2019)
This research discussed the teachers’ acceptance towards the inclusive education program. The purpose of the research was to identify how the teachers accept the program for students with hearing disabilities. This research was also conducted to gather suggestions on ways to improve the program through the gatherings of opinions from these teachers. Thirty mainstream teachers from a school in Melaka were chosen as respondents based on the criteria that their school has an integrated program for students with hearing disabilities and applies this program to these students in classes. Data was collected by randomly distributing questionnaires to respondents and analyzed using the Statistical Package for Social Science (SPSS V22). The research result showed that teachers accept the inclusive education program positively. This research put forward suggestions as guidelines to the public and hopes that in the future more research could be done on this program with multiple objectives and concepts.